Intelligent Forecasting and Optimization in Electrical Power Systems - Piotrowski, Paweł; Dudek, Grzegorz; Baczyński, Dariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint explores the latest developments and advancements in the application of artificial intelligence (AI) and machine learning (ML) for forecasting and optimization in the field of power engineering. In recent years, AI and ML methods have been gaining significant traction and are becoming two of the most important fields in computing. These methods have proven to be effective in solving forecasting and optimization problems in power engineering. The topics covered in the chapters fall into four categories: electricity demand forecasting, wind power forecasting, photovoltaic power forecasting, and optimization.